Multiplex PCR method to detect Cyclospora, Cystoisospora, and Microsporidia in stool samples - Taniuchi, Mami (2011)
Cyclospora, Cystoisospora, and Microsporidia are eukaryotic enteropathogens that are difficult to detect in stool samples because they require special stains and microscopy. We developed a multiplex PCR reaction with 4 primer sets to amplify Cyclospora cayetanensis, Cystoisospora belli, Enterocytozoon bieneusi, and Encephalitozoon intestinalis. Detection of the amplicon is through specific probes coupled to Luminex beads. Sensitivity of the assay was evaluated using Encephalitozoon intestinalis spores and revealed detection of 10(1) spores spiked into stool. No cross reactivity was observed. We evaluated the assay on diarrheal specimens from Thailand, Tanzania, Indonesia, and the Netherlands that had been previously tested by microscopy and the assay yielded 87–100% sensitivity and 88–100% specificity. Microscopy negative/PCR positive samples had lower Luminex values suggesting they were true but lower burden infections. In summary this is a convenient single PCR reaction that can detect Cyclospora, Cystoisospora, and Microsporidia without the need for cumbersome microscopic analysis.